Reciprocal interactions across and within multiple levels of monoamine and cortico-limbic systems in stress-induced depression: A systematic review. (June 2019) - Lee, Eun-Hwa; Han, Pyung-Lim
Highlights: Chronic stress changes neural activity of cortico-limbic regions and monoamine systems. Monoamine and non-monoamine systems are reciprocally interactive at multiple levels. Reshaping altered neural activity dynamics reverses depressive-like behaviors. Abstract: The monoamine hypothesis of depression, namely that the reduction in synaptic serotonin and dopamine levels causes depression, has prevailed in past decades. However, clinical and preclinical studies have identified various cortical and subcortical regions whose altered neural activities also regulate depressive-like behaviors, independently from the monoamine system. Our systematic review indicates that neural activities of specific brain regions and associated neural circuitries are adaptively altered after chronic stress in a specific direction, such that the neural activity in the infralimbic cortex, lateral habenula and amygdala is upregulated, whereas the neural activity in the prelimbic cortex, hippocampus and monoamine systems is downregulated. The altered neural activity dynamics between monoamine systems and cortico-limbic systems are reciprocally interwoven at multiple levels. Furthermore, depressive-like behaviors can be experimentally reversed by counteracting the altered neural activity of a specific neural circuitry at multiple brain regions, suggesting the importance of the reciprocally interwoven neural networks in regulating depressive-like behaviors. These results promise for reshaping altered neural activity dynamics as a therapeutic strategy for treating depression.